Effectiveness of Gotu Kola Extract Lotion (Centella Asiatica) in Reducing Stretch Marks - Indria Nuraini; Asti Rahayu (Jurnal Ilmiah Kesehatan, 2021)
Stretch marks result from mechanical factors, namely stretching of the skin due to the development of subcutaneous structures (interstitial adipose tissue) or biochemical factors (the presence of excessive glucocorticoids that inhibit fibroblast activity and proliferation). There is no truly effective treatment for removing striae once they have formed. This study evaluates the effectiveness of administering Gotu Kola Extract (Centella asiatica) on the stretch mark. This paper was a Quasi-Experimental study with a pretest-posttest design. This study was conducted at the Independent Practice Midwife (IMP) Zummatul Atika in October-December 2020. The population was postpartum mothers (days 0-6) with stretch marks. Meanwhile, there were 12 respondents by purposive sampling technique. The independent variable was Gotu kola extract lotion, while the dependent variable was stretch marks with ratio data. Collecting data with a structured interview to gather the characteristics of respondents and participant observation to evaluate changes (number of stretch marks, color, moisture, and skin condition) in stretch marks before and after intervention during one month. The Gotu kola extract lotion was made in the pharmacy laboratory of PGRI Adi Buana University Surabaya within several stages. The data analysis used the paired T-test, and the result showed p= 0.000, indicating a significant difference before and after the intervention. This study concludes that administering Gotu Kola Extract (Centella asiatica) lotion effectively reduces skin pigmentation and lines in stretch marks, increases skin moisture, and refines skin texture.